Production of biofertilizer from vermicomposting process of municipal sludge - Siti Zahirah, Zulkapri (2011)
The potential of the epigeic tiger worms ( Eisenia fetida) in this study is aimed at safe reuse and recycling of municipal sewage sludge (MSS) in vermicomposting process and the major nutrient status, its simple vermicompost were assessed across different periods in relation to its respective initiative substrates. The present study aims to find out the possibility of utilization of sewage sludge for vermiculture. 1000 g of tiger worms were cultured in plastic container (0.55 wide x 0.30 high x 0.25 long) metre containing 25000 g sewage sludge. The optimum daily feeding rate of sludge is equal to the weight of worm biomass in the bin. This bin was used to calculate the sludge volume reduction by vermicomposting process and it was determined that there is a nearly 90% of volume reduction. Their physical parameters – temperature and moisture is maintained also the pH is decreased (alkali to acidic) during the vermicomposting process, were recorded. The nutrients –total nitrogen (TN), Total phosphorus(TP), and Total potassium(TK) in the vermicast as the process progressed from 0 to 1, 7, 14 and 21 days were also obtained. It was found that the vermicast are rich in nutrients of Nitrogen, Phosphorus and Potassium. The present study also inferred that the application of sewage sludge can be reused and retreated as a good quality biofertilizer in agricultural fields after vermicomposting would not have any adverse effect to the environmental. Results indicate that vermicomposting might be useful for managing the energy and nutrient rich sewage sludge on a low-input basis. Products of this process can be used for sustainable land restoration practices. The feasibility of tiger worms may also reduces the possibility of soil contamination. The advantages of this concept are high performance, easy collection of compost and long run without cleaning. Worms were also produced as a very useful by-product.